Molecular organization of small plasmids bearing blaTEM-1 and conferring resistance to β-lactams in Haemophilus influenzae. - Søndergaard, A; San Millan, A; Santos-Lopez, A; Nielsen, S; Gonzalez-Zorn, B; Nørskov-Lauritsen, N (2012)
TEM-1 is the dominant β-lactamase of Haemophilus influenzae and can be located on small plasmids. Three distinct plasmids with sizes from 4,304 to 5,646 nucleotides (nt) were characterized: pA1606, pA1209, and pPN223. In addition to TEM-1 and a replication enzyme of the Rep 3 superfamily, pA1606 carries a Tn3 resolvase gene and pA1606 and pA1209 carry an open reading frame (ORF) similar to a plasmid recombination enzyme gene described in Gram-positive bacteria. The plasmids transformed strain Rd to the ampicillin-resistant phenotype.